2022
DOI: 10.3390/ani12070917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postbiotics and Paraprobiotics as Replacements for Antibiotics on Growth Performance, Carcass Characteristics, Small Intestine Histomorphology, Immune Status and Hepatic Growth Gene Expression in Broiler Chickens

Abstract: Background: This experiment was designed to investigate how replacing antibiotics with postbiotics and paraprobiotics could affect growth performance, small intestine morphology, immune status, and hepatic growth gene expression in broiler chickens. Methods: The experiment followed a completely randomized design (CRD) in which eight treatments were replicated six times with seven birds per replicate. A total of 336, one-day-old (COBB 500) chicks were fed with the eight treatment diets, which include T1 = negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…These results are in line with those of Xiao et al 28 and Hand 29 , who discovered that the anti-vaccine titre of birds that had been given killed probiotic treatment was significantly higher than that of control birds. On the other hand, according to Donaldi et al 25 , there were no appreciable differences in immune response when paraprobiotic or postbiotic supplementation was combined with a basal diet. According to this study, intake paraprobiotics significantly influenced immune system related organs like the spleen and thymus.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results are in line with those of Xiao et al 28 and Hand 29 , who discovered that the anti-vaccine titre of birds that had been given killed probiotic treatment was significantly higher than that of control birds. On the other hand, according to Donaldi et al 25 , there were no appreciable differences in immune response when paraprobiotic or postbiotic supplementation was combined with a basal diet. According to this study, intake paraprobiotics significantly influenced immune system related organs like the spleen and thymus.…”
Section: Discussionmentioning
confidence: 92%
“…When contrasted with the control and other treated groups, the T 5 and T 6 groups' birds had the lowest FCR values. The results of Danladi et al 25 are at odds with this because they discovered no appreciable modifications to broiler diets following the addition of paraprobiotics to the diet. The results of this study corroborate those of Humam et al 26 , who reported improved FCR after dietary supplementation with paraprobiotic and postbiotic bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…These results are in line with those of Xiao et al 24 and Hand 25 , who discovered that the anti-vaccine titre of birds that had been given killed probiotic treatment was signi cantly higher than that of control birds. On the other hand, according to Donald et al 21 , there were no appreciable differences in immune response when paraprobiotic or postbiotic supplementation was combined with a basal diet. According to this study, intake paraprobiotics signi cantly in uenced of immune system related organs like the spleen and thymus.…”
Section: Discussionmentioning
confidence: 93%
“…When contrasted with the control and other treated groups, the T 5 and T 6 groups' birds had the lowest FCR values. The results of Danlad et al 21 are at odds with this because they discovered no appreciable modi cations to broiler diets following the addition of paraprobiotics to the diet. The results of this study corroborate those of Humam et al 22 , who reported improved FCR after dietary supplementation with paraprobiotic and postbiotic bacteria.…”
Section: Discussionmentioning
confidence: 96%
“…The ‘postbiotic’ has emerged which extends the scope of the probiotic concept beyond its inherent viability [ 9 ]. The term ’postbiotic’ refers to the soluble factors (stabilized bacteria, cellular products, or metabolic by-products) secreted by living microbes or released after microbial lysis [ 10 ], which are mainly derived from Lactobacillus , Bifidobacterium , Streptococcus , fecal bacteria [ 11 , 12 ], and Saccharomyces cerevisiae yeast [ 13 , 14 ]. Recent research suggests that postbiotics offer various health benefits through immune system modulation (cell wall compounds may strengthen immunity), increased adhesion to intestinal cells (which restricts pathogen growth), and secretion of various metabolites [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%